Correlation between Agility and Speed in Elite Underwater Hockey Players - (:unkn) unknown (INT JOURNAL APPLIED EXERCISE PHYSIOLOGY, 2020)
The correlation between in-pool agility and sprint tests has not been established in underwater sports. The purpose of this study was therefore to investigate the correlation between in-pool agility tests [T-test (Tt), Modified T-test (MTt] and in pool sprint tests [25m (S25m), 50m (S50m)] in national level male elite underwater hockey players. This study was conducted on 25 male national level underwater hockey athletes. Tests were underwent in pool with ambient temperature of 25 degrees +/- 10 Celsius degrees and water temperature of 27 degrees Celcius degrees. Agility tests and sprint tests were performed on separate days at least 24 hours apart. Tt was performed on the surface of the water and MTt was performed underwater using underwater video recording and signaling apparatus. The descriptive values were expressed as mean and standard deviation. Normal destribution of data examnined using Shapiro-Wilk and Levene tests. The Pearson's linear correlation test was applied to calculate the correlation. The significance level was set to P<0.05. There was a positive strong correlation existed between Tt and Mt, value of correlation was r=0.900, p=0.000. The Pearson's test shows significant positive high correlation between Tt and S50m, value of correlation was r=0.600, p=0.002. In contrast, MTt showed no significant correlation with S50m. The Pearson's test also showed significant positive moderate correlation between Tt and S25m, value of correlation was r=0.580, p=0.002. MTt was significantly correlated with S25m (r=0.512, p=0.009). The results of this study revealed moderate to stong correlation between in-pool agility and sprint tests.
Keywords: Underwater; Hockey Players; Speed; Agility; ANTHROPOMETRIC CHARACTERISTICS; REACTIVE AGILITY; ENERGY-COST; T-TEST; PERFORMANCE; DETERMINANTS; SWIMMERS; VALIDITY; NETBALL; ABILITY